Advanced novel carbon nanomaterials for the development of single-phase induction motor rotor: A simulation investigation of the electrical performance with different materials - Atazaz Hassan; Sajid Abbas; Zigang Deng; Chen Quanfang; Luo Youming; Li Wang; Muhammad Shahid Mastoi (Results in Engineering, 2025)
Increasing global energy efficiency and environmental sustainability demands necessitate alternative rotor materials for single-phase induction motors (SPIM) because copper and aluminum materials lead to significant problems with power wastage, environmental degradation, and constrained resource availability. The research derives from an immediate necessity for advanced sustainable materials that improve motor operation and support eco-friendly engineering frameworks. The simulation experiments explore the alternative usage of novel carbon nanomaterials such as carbon nanotubes (CNT), carbon nanotube aluminum (CNT/Al), and carbon nanotube copper (CNT/Cu) composite wires to replace conventional conductive materials in SPIM rotor applications. A finite element method (FEM)-based modeling platform known as COMSOL Multiphysics examines the electrical characteristics of SPIMs containing these nanomaterials during an analysis of the torque, electromagnetic losses, induced coil voltage, power, and efficiency. Implementing material models utilizes experimental data from valid literature sources to achieve accurate simulation results. According to the numerical findings, the CNT, CNT/Al, and CNT/Cu rotor winding prototype motor torques are 0.24 N.m, 0.36 N.m, and 0.53 N.m, respectively. In addition, the numerical simulation testing results demonstrate that using CNT, CNT/Al, and CNT/Cu conductors as rotor winding material gives better efficiencies of 66 %, 80 %, and 85 %, respectively. The CNT-Cu composite windings demonstrate promising results in tests through enhanced efficiency and torque performance with reduced losses and weight. The obtained results shed light on the potential use of novel carbon nanomaterials and lay out the direction for developing advanced materials for electrical machines. In addition to enhancing electrical performance, this finding adds to the general sustainable engineering agenda by advocating low-carbon and high-performance replacements of conventional materials. The implications of these findings extend to larger issues such as the future of electric motors as well as other green technologies in renewable energy systems, the future of electric vehicles, and energy policy trends of decreasing dependence on finite natural resources.